POEM: prediction of immunogenic epitopes using mechanistic modelling of the MHC class I antigen processing pathway - Weatherseed, M (2024)
Existing machine learning algorithms predicting class I antigen presentation are fundamentally awed due to the nature of the immunopeptidomics data used for their training. These models, rather than predicting antigen abundance, primarily indicate the presence of antigens on the cell surface. In this thesis, we integrate machine learning with mechanistic modelling to develop an enhanced model of the class I antigen processing pathway.